Le traitement médiatique des drogues dans la presse quotidienne française (2013-2018) - Cécilia Comelli (Pôle de Recherche pour l'Organisation et la diffusion de l'Information Géographique, 2021)
The media have become objects of study and tools increasingly used by the humanities and social sciences. The discourses conveyed by the latter participate in shaping social representations, spatial representations and geographical imaginaries. This article has a double ambition: on the one hand, to present a tool and a method of analysis of the press in terms accessible to non-specialists of textual analysis and, on the other hand, to present the results obtained thanks to this method to the question: which thematic and spatial treatments of drugs in the French daily press? We thus sought to know what thematic were chosen by the newspapers and what geography(ies) of drugs could be identified from this media treatment. These two entries provide information on the political context and on the representations conveyed by and around this sensitive object of study.